Implementasi Model Pembelajaran Quantum dengan Metodediskusi untuk Meningkatkan Aktivitas dan Hasil Belajar Fisika Siswa SMPN 2 Lingsar Tahun Ajaran 2014/2015 - Ibrohim Mirgoni; Hairunnisyah Sahidu; Hikmawati Hikmawati (Department of Physics Education, Universitas Mataram, 2015)
This research is a classroom action research which aims to increase physical activity and learning outcomes of students SMPN 2 Lingsar the academic year 2014/2015. The subjects in this study VIII5 classes totaling 40 people. Implementation of classroom action research was conducted in two cycles with each cycle consisting of four stages: planning, implementation, observation and evaluation, and reflection. Student learning activity data obtained through observation, while data on student learning outcomes obtained through the administration of the test at the end of each cycle. Based on the results of the evaluation cycle I obtained an average score of student learning activity is 11, which is in the category fairly active. The average value of the class in the first cycle of 73.95 with 78.95% classical completeness. Results of the evaluation in the second cycle to the average score is 14.6 students' learning activities that are in the active category. The average value of the class in the second cycle of 78.10 with 89.19% classical completeness. The average score of student learning activity increased from the first cycle to the second cycle of 3.6, the learning outcomes of students increased by 4.15, while the classical completeness increased by 10.24%. Based on the results of this study concluded that the implementation of the learning model Quantum with discussion method can increase physical activity and learning outcomes VIII5 grade students of SMPN 2 Lingsar the academic year 2014/2015.